Part of speech tagger for non-standardized Malay text in social media / Nur Syamimi Ardenan - Ardenan, Nur Syamimi (2022)
This chapter provide an overview background of this project. It includes defining the problem statement, project objectives, project scope, and significance that led to this project. As an introduction, this project is a web-based application that normalised a non-standardised Malay text in part-of-speech using Hidden Markov Model. A proposed solution was summarized in the problem statement.